Economia criativa de audiovisual do Brasil: ascensão dos streamings e o desenvolvimento regional - Neves, Maria Clara Almeida (2025)
The study analyzes the impact of the expansion of streaming platforms on the Brazilian audiovisual market, highlighting their contribution to strengthening the creative economy, developing technologies for digital production and distribution, and fostering the growth of the audiovisual industry. The research adopts a qualitative approach and is organized into three chapters that explore technological innovation in the sector, the arrival and consolidation of streaming platforms in Brazil, and a case study on Netflix. Additionally, it examines how the geographical concentration of production companies contracted for original productions influences regional development and the distribution of investments in the audiovisual sector. As a relatively recent technology, streaming initially emerged as a digital media distribution service and, over the past decade, has established itself as a popular format for media consumption, becoming an alternative to physical formats and traditional television. Thus, the study explores how the evolution of streaming platforms modifies media consumption habits and stimulates regional development. The research revealed that the rise of streaming platforms in Brazil has transformed the audiovisual sector, stimulating the production of national content and expanding access to a greater diversity of works. However, foreign productions still dominate consumption, and despite the growth of Brazilian productions on streaming platforms, investments remain concentrated in the Rio-São Paulo axis, limiting the expansion of audiovisual hubs in other regions.